(untitled) (Bangladesh Journal of Animal Science, 2020)
The objective of this study was to evaluate the physical and chemical value addition to rice straw on nutritional quality improvement of rice straw and its effect on milk productivity and composition. Twelve crossbred milking cows (Frisian Cross) of mid-lactation stage and second parity, having average initial body weight of 398.72 ± 42.22 kg and milk yield of 6.42± 0.78 kg were assigned to three treatment group (each group has 4 animals) and one control group. Four treatments were considered: T0 (control): loose rice straw + green grass + concentrate; T1: value addition to rice straw through chopping (physical) + green grass + concentrate; T2: value addition to rice straw through urea and molasses without chopped (Chemical) + green grass + concentrate; and T3: value addition to rice straw through urea molasses with chopping (Physical and chemical) + green grass + concentrate. The results revealed that T2 was significantly (p<0.05) higher than T0, T1 and T3 where total DM intake was 13.44± 0.26, 12.96±0.38, 12.47±0.16 and 12.06±0.31 for T2, T0, T3 and T1, respectively and the same was found for Crude protein. The daily milk yield was higher in T3 (8.12±0.30 kg/day) and followed by T0 (7.30±0.23 kg/day), T1 (6.61±1.35 kg/day) and T2 (6.78±0.09 kg/day) but daily milk yield gains were 0.31, 0.11, 1.44 and 1.46 kg in T0, T1, T2, and T3, respectively and differences were highly significant (p<0.01) among the groups. Milk composition of fat (4.40, 3.97, 4.90 and 4.10%), Protein (3.88, 3.69, 3.98 and 3.72%), SNF (8.42, 8.69, 8.49 and 8.13) and TS (12.57, 12.34, 12.96 and 11.90) in T0, T1, T2 and T3, respectively. There was significant difference (p<0.01) where the cows supplemented with UMS without and with chopping recorded SNF. Further study might be needed to estimate the economics of the value addition for enhancing the adoption of this technology at farm level through development of entrepreneurship. Bang. J. Anim. Sci. 2020. 49 (1): 55-62